A study of students’ motivation using the augmented reality science textbook - Gopalan, Valarmathie; Zulkifli, Abdul Nasir; Abu Bakar, Juliana Aida (2016)
Science plays a major role in assisting Malaysia to achieve the developed nation status by 2020. However, over a few decades, Malaysia is facing a downward trend in the number of students pursuing careers and higher education in science related fields. Since school is the first platform where students learn science, a new learning approach needs to be introduced to motivate them towards science learning. The aim of this study is to determine whether the intervention of the enhanced science textbook using augmented reality contributes to the learning process of lower secondary school students in science.The study was carried out among a sample of 70 lower secondary school students.Pearson Correlation and Regression analyses were used to determine the effects of ease of use, engaging, enjoyment and fun on students’ motivation in using the augmented reality science textbook for science learning. The results provide empirical support for the positive and statistically significant relationship between engaging, enjoyment and fun and students’ motivation for science learning. However, Ease of use is not significant but positively correlated to Motivation.